Implementation of a Multicultural Value System in the Islamic Religious Education Curriculum at Muassasah Mahad Ats-Tsaqofah Al-Islamiyah, Poming Pattani, Thailand - Abdul Basyit; Muh Turizal Husein; Nasrulloh Nasrulloh; J Anhar Rabi Hamsah Tis’ah; M. Dahlan R.; Achmad Fauzi (STAI Hubbulwathan Duri, 2023)
This study aims to analyze, identify, and validate the implementation of a multicultural value system within the Islamic religious education curriculum at Muassasah Mahad Ats-Tsaqofah Al-Islamiyah, Poming Pattani, Thailand. Conducted as field research with a qualitative approach, the study utilizes methods that are inherently naturalistic, collecting and analyzing qualitative data from both primary and secondary sources. Primary data were gathered through direct field observations, interviews with school principals, Islamic Religious Education (PAI) teachers, and deputy heads of curriculum, and documentation of the institution’s history, profiles, and educational practices. Secondary data supplemented these findings with existing literature, documents, photographs, and statistics. The research setting includes detailed observations of the geographical location and physical conditions of the institution, learning activities aimed at instilling multicultural values, and the available educational facilities and infrastructure. The data analysis process involved reducing data to identify key themes, presenting the data through various formats, verifying findings through techniques like source and technical triangulation, and extension of observations. The results indicate that Muassasah Mahad Ats-Tsaqofah Al-Islamiyah has effectively integrated multicultural education into its Islamic religious education curriculum by embedding multicultural values into existing materials and activities. This integration has been thorough and deep, promoting values of tolerance, equality, and unity among students, contributing to a more inclusive and harmonious educational environment.